Special paperCurrent standards for diagnosis and treatment of syphilis: selection of some practical issues, based on the European (IUSTI) and U.S. (CDC) guidelines - Pastuszczak, Maciej; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Syphilis continues to be an important epidemiologic problem. For a few years a steady increase in the incidence of this sexually transmitted disease has been observed. Advances in medical science obligate the doctor to use only such diagnostic and therapeutic approaches that are scientifically proven. Based on the European (IUSTI) and U.S. (CDC) guidelines, in this manuscript, we present some selected practical issues concerning diagnosis and treatment of syphilis. We truly hope that the present review will help all doctors taking care of syphilitic patients to systematize the current knowledge.